Poly(phenol red) hierarchical micro-structure interface enhanced electrode kinetics for adsorption and determination of hydroquinone. (1st May 2021) - Promsuwan, Kiattisak; Kaewjunlakan, Chompoonut; Saichanapan, Jenjira; Soleh, Asamee; Saisahas, Kasrin; Thipwimonmas, Yudtapum; Kongkaew, Supatinee; Kanatharana, Proespichaya; Thavarungkul, Panote; Limbut, Warakorn
Highlights: Poly(phenol red) micro-structure was electropolymerized by cyclic voltammetry. The modified electrode improved electrocatalytic oxidation and adsorption kinetics. The modified electrode determined hydroquinone via stripping voltammetry. The electrode was used to determine hydroquinone in skin whitening products. Abstract: A simple, new strategy for enhancing the electrochemical adsorption and determination of hydroquinone was proposed that involved modifying a glassy carbon electrode with a hierarchical structure of poly(phenol red) microparticles (P(PhR)MPs electrode). The electrochemical oxidation of hydroquinone at the P(PhR)MPs electrode displayed quasi-reversible behavior. The electrocatalysis and adsorption kinetics of the P(PhR)MPs toward hydroquinone were proved using chronoamperometry and EIS. Hydroquinone was determined by the P(PhR)MPs electrode at concentrations from 10 ng mL −1 to 100 μg mL −1 (91 nmol L −1 to 908 μmol L −1 ) using adsorptive anodic stripping voltammetry (AdASV) with an accumulation time of 30 s. Electrode sensitivity was 3.54 μA μg −1 mL cm −2, and limits of detection (LOD) and quantitation (LOQ) were 2.7 ng mL −1 (25 nmol L −1 ) and 10 ng mL −1 (91 nmol L −1 ), respectively. The P(PhR)MPs electrode preparation exhibited good repeatability (RSDs between 1.66 and 3.87% ( n = 15)), good reproducibility (RSD < 3.2% n = 6) and excellent anti-interference properties. The proposed method successfully quantified hydroquinone in skin whitening products with recoveries between 93 ± 2 and 102 ± 1% and there was no significant difference at a 95% confidence level between the results from the proposed sensor and those from UV-derivative spectrophotometry. The developed poly(phenol red) hierarchical micro-structure showed that it could be used as an interface for application in electrochemical sensors or biosensors. Graphical abstract: Image, graphical abstract